Effect of the herbal medicines in obesity and metabolic syndrome: A systematic review and meta‐analysis of clinical trials. (2nd December 2019) - Payab, Moloud; Hasani‐Ranjbar, Shirin; Shahbal, Nazila; Qorbani, Mostafa; Aletaha, Azadeh; Haghi‐Aminjan, Hamed; Soltani, Akbar; Khatami, Fatemeh; Nikfar, Shekoufeh; Hassani, Shokoufeh; Abdollahi, Mohammad; Larijani, Bagher
Abstract : Obesity is a medical situation in which excess body fat has gathered because of imbalance between energy intake and energy expenditure. In spite of the fact that the variety of studies are available for obesity treatment and management, its "globesity" still remains a big challenge all over the world. The current systematic review and meta‐analysis aimed to evaluate the efficacy, safety, and mechanisms of effective herbal medicines in the management and treatment of obesity and metabolic syndrome in human. We systematically searched all relevant clinical trials via Web of Science, Scopus, PubMed, and the Cochrane database to assess the effects of raw or refined products derived from plants or parts of plants on obesity and metabolic syndrome in overweight and obesity adult subjects. All studies conducted by the end of May 2019 were considered in the systematic review. Data were extracted independently by two experts. The quality assessment was assessed using Consolidated Standards of Reporting Trials checklist. The main outcomes were anthropometric indices and metabolic syndrome components. Pooled effect of herbal medicines on obesity and metabolic syndrome were presented as standardized mean difference (SMD) and 95% confidence interval (CI). A total of 279 relevant clinical trials were included. Herbals containing green tea, Phaseolus vulgaris, Garcinia cambogia, Nigella sativa, puerh tea, Irvingia gabonensis, and Caralluma fimbriata and their active ingredients were found to be effective in the management of obesity and metabolic syndrome. In addition, C. fimbriata, flaxseed, spinach, and fenugreek were able to reduce appetite. Meta‐analysis showed that intake of green tea resulted in a significant improvement in weight ([SMD]: −0.75 [−1.18, −0.319]), body mass index ([SMD]: −1.2 [−1.82, −0.57]), waist circumference ([SMD]: −1.71 [−2.66, −0.77]), hip circumference ([SMD]: −0.42 [−1.02, −0.19]), and total cholesterol, ([SMD]: −0.43 [−0.77, −0.09]). In addition, the intake of P. vulgaris and N. sativa resulted in a significant improvement in weight ([SMD]: −0.88, 95 % CI: [−1.13, −0.63]) and triglyceride ([SMD]: −1.67, 95 % CI: [−2.54, −0.79]), respectively. High quality trials are still needed to firmly establish the clinical efficacy of the plants in obesity and metabolic syndrome.